Climate Through a Local Lens: A Study of Rajbanshi Indigenous Knowledge - Khanal, Sushil Kumar (Adhyayan Journal, 2026)
As our world is combating the new challenges of climate change, the indigenous community possesses traditional knowledge that contributes valuable insights to the study area. In this context, this study explores the climatic knowledge of the Rajbanshi community in Jhapa district of Nepal on the basis of a local lens. The research design is explorative with an ethnographic study. The data collection procedures include unstructured interviews, key informant interviews, participant observation, and focus group discussions, which reveal the community’s perception of climate change and their adaptive strategies. As research findings reveal a wider indigenous knowledge, including seasonal forecasting, traditional agricultural practices, and resource management techniques among the Rajbanshi community, transmitted through intergenerational interaction by engaging in social interaction and cultural practices. It also discloses that the Rajbanshi people have a dynamic capacity to adapt to new and changing environmental conditions. Identifying the importance of indigenous knowledge for climate change adaptation and resilience plays a vital role in climate policy and programs for adaptation and resilience.